Experimental study on 3D internal penny‐shaped crack propagation in brittle materials under uniaxial compression - Jiyun Xu; Hanzhang Li; Haijun Wang; Lei Tang (Deep Underground Science and Engineering, 2023)
Abstract Fractures are widely present in geomaterials of civil engineering and deep underground engineering. Given that geomaterials are usually brittle, the fractures can significantly affect the evaluation of underground engineering construction safety and the early warning of rock failure. However, the crack initiation and propagation in brittle materials under composite loading remain unknown so far. In this study, a three‐dimensional internal laser‐engraved cracking technique was applied to produce internal cracks without causing damage to the surfaces. The uniaxial compression tests were performed on a brittle material with internal cracks to investigate the propagation of these internal cracks at different dip angles under compression and shear. The test results show that the wing crack propagation mainly occurs in the specimen with an inclined internal crack, which is a mixed‐Mode I–II–III fracture; in contrast, Mode I fracture is present in the specimen with a vertical internal crack. The fractography characteristics of Mode III fracture display a lance‐like pattern. The fracture mechanism in the brittle material under compression is that the internal wing cracks propagate to the ends of the whole sample and cause the final failure. The initial deflection angle of the wing crack is determined by the participation ratio of stress intensity factors KII to KI at the tip of the internal crack.